(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Literature depicts Small and Medium Enterprises (SMEs) play a dominating role in improving the economic status of a country, especially in developing countries. However, access to credit is a major problem which SMEs face worldwide. The problem of financing is dealt by offering of different financial products like bank loan, line of credit by the banks to the SMEs. As marketing communicates the potential clients about the products and services, it is crucial to understand SMEs viewpoint towards marketing financial products. Hence, the present study attempts to capture the perspectives (i.e., benefits and associated risks) of people associated with SMEs and SMEs’ owners towards the marketing of financial products in a developing country like Bangladesh.